Optimalisasi Manajemen SDM Berbasis Nilai-Nilai Syariah dalam Meningkatkan Kinerja Karyawan pada Lembaga Keuangan Syariah - Dhani Sudirman; Asep Khaerul Faizin; Dede Sugandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Human resource (HRM) management in Islamic financial institutions emphasizes not only efficiency and productivity but also reflects Islamic values in all its practices. This study aims to examine how optimization of HRM based on Sharia values is carried out at Pegadaian Syariah Johar, East Karawang, and how this implementation impacts employee performance. This study uses a descriptive qualitative approach with a case study method. Data collection techniques were conducted through observation, in-depth interviews, and documentation of management and employees directly involved in institutional activities. The results show that Sharia values such as trustworthiness, honesty, responsibility, and deliberation have been internalized in the work culture and interpersonal relationships among employees. Although not yet fully integrated into formal managerial systems such as recruitment and performance evaluation, these values have positively contributed to employee discipline, loyalty, and work ethic. These findings confirm that a values-based approach can be an effective strategy for managing HRM in Islamic financial institutions. The implications of this research encourage the importance of developing a more structured and consistent HR management system with sharia principles, so that Islamic financial institutions are not only economically superior, but also reflect ethical and spiritual excellence.